PERSEPSI PENGGUNA TERHADAP KUALITAS RUANG TERBUKA PUBLIK PELATARAN MASJID GEDHE KAUMAN MELALUI PENDEKATAN PLACEMAKING - Saputra, Wahyu; Sarwadi, Ahmad (Universitas Aisyiyah Yogyakarta, 2019)
The role of the city's public open space has been recognized and accepted as the main asset of a sustainable city. The Kauman Gedhe Mosque Pelataran is a public open space that has been a place for various profane and sacred activities of the people of Yogyakarta. The method used in this research is survey technique, data collected by distributing questionnaires online via google form and manual questionnaires. The results of this study indicate that from the four aspects of perceptions of space users measured, the image and accessibility of the Kauman Gedhe Mosque Pelataran has high quality values rather than aspects of security and comfort.